Control of the reversibility during boronic ester formation: application to the construction of ferrocene dimers and trimers. Issue 7 (31st January 2017) - Ono, Kosuke; Tohyama, Yohei; Uchikura, Tatsuhiro; Kikuchi, Yuji; Fujii, Kotaro; Uekusa, Hidehiro; Iwasawa, Nobuharu
Abstract : Equilibration of boronic esters during boronic ester formation was controlled using protic or aprotic solvents under neutral conditions. Abstract : Control of the reversibility during boronic ester formation from boronic acids and diols was found to be possible by choosing an appropriate solvent. As an example, ferrocene dimers and trimers were constructed by using tetrol1 with an indacene framework, 1, 1′-ferrocenediboronic acid2, and ferrocenemonoboronic acid4 . When equimolar amounts of1 and2 were mixed in methanol under equilibrating conditions, two kinds of stacked ferrocene dimers homo - and hetero -3 were selectively obtained depending on the reaction time and both structures were determined by X-ray crystallographic analysis. On the other hand, the ferrocene trimer7 was successfully constructed by stepwise assembly in the presence of anhydrous magnesium sulfate in acetone where the equilibration of boronic esters was suppressed, while no formation of ferrocene trimer7 was detected when all components1, 2 and4 (2 : 1 : 2 ratio) for trimer7 were mixed at a time in methanol under equilibrating conditions.